The efficiency of intersectionality: labelling the benefits of a rights-based approach to interpret sexual and gender-based crimes - Martin, Ana (Human rights review, 2024)
International criminal law (ICL) has traditionally overlooked sexual and gender-based violence (SGBV) and struggles to understand it. Prosecutions have been largely inefficient and not reflective of gender harms. The Rome Statute requires interpreting SGBV as a social construction (article 7(3)), in consistency with international human rights law (IHRL) and without discrimination (article 21(3)). There is, however, little guidance to implement these approaches. This article argues that intersectionality, an IHRL-based approach that reveals compounded discrimination, is an efficient tool to interpret SGBV and, therefore, should be integrated in ICL. The article traces the origins of intersectionality in feminism and its recognition by IHRL dealing with violence against women. It establishes the applicability of intersectionality in ICL that it demonstrates with a comparative analysis of the Lubanga and Ntaganda cases. The findings show that intersectionality suits ICL’s specific needs which allows labelling and explaining some of those contributions throughout the judicial process.